1973
DOI: 10.1021/jo00941a001
|View full text |Cite
|
Sign up to set email alerts
|

Arylsuflonoxylation of aromatic compounds. III. Kinetics of the nitrophenylsulfonoxylation of alkylbenzenes

Abstract: The m-and p-nitrophenylsulfonoxylation of alkylbenzenes in ethyl acetate solution is first order in peroxide and is not acid catalyzed. Although simple first-order kinetics with respect to alkylbenzenes are observed, with benzene itself the reaction first order with respect to arene competes with a reaction of the peroxide which is zero order with respect to the aromatic. In methylene chloride, arylsulfonoxylation gives simple first-order kinetics with respect to benzene as well as toluene and ethylbenzene. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1975
1975
2001
2001

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Ph.,B-CHC1" 2. NaOH-H.O, 5" 23 been used to oxidize triarylboranes to the corresponding boric esters.11 This suggested that a triarylborane, such as the commercially available triphenylborane,12 could be used to reduce amine oxides to the corresponding amines under nonhydrolytic conditions. Indeed, treatment of 22 with triphenylborane in chloroform at room temperature followed by treatment with cold, aqueous sodium hydroxide solution afforded a 79% yield of trans 13 This facile hydrolysis of 23 is in accord with our proposal that aminocyclopropyl sulfones are intermediates in the aqueous potassium permanganate oxidation of aminocyclopropyl sulfides.…”
supporting
confidence: 86%
“…Ph.,B-CHC1" 2. NaOH-H.O, 5" 23 been used to oxidize triarylboranes to the corresponding boric esters.11 This suggested that a triarylborane, such as the commercially available triphenylborane,12 could be used to reduce amine oxides to the corresponding amines under nonhydrolytic conditions. Indeed, treatment of 22 with triphenylborane in chloroform at room temperature followed by treatment with cold, aqueous sodium hydroxide solution afforded a 79% yield of trans 13 This facile hydrolysis of 23 is in accord with our proposal that aminocyclopropyl sulfones are intermediates in the aqueous potassium permanganate oxidation of aminocyclopropyl sulfides.…”
supporting
confidence: 86%
“…6 Rate of electrophilic aromatic substitution relative to benzene. cData taken from series of papers by Dannley and co-workers given in ref16. dData taken from de la Mare, P. B. D.; Ridd, J. H Aromatic Substitution, Nitration and Halogenation•, Academic Press: New York,1959.…”
mentioning
confidence: 99%
“…the m-trifluoromethylphenylsulfonoxylation in ethyl acetate of benzene (based on overall &i), ethylbenzene, and cumene (Table V) are all about 1 kcal greater and the entropies of activation only a little less negative than the corresponding values for the m-and pnitrophenylsulfonoxylation of the arenes. 13 This reflects the somewhat greater stability and longer half-lives of reaction of the trifluoromethyl peroxide observed in the laboratory as compared to the data for the nitro peroxides.…”
Section: Resultsmentioning
confidence: 94%
“…A similar rela-tionship was observed for the nitrophenylsulfonoxylations of the arenes. 13 The large negative entropies of activation for all the bimolecular arylsulfonoxylations are to be expected for electrophilic substitutions. The large positive entropy of activation for the &2 m-trifluoromethylphenylsulfonoxylation of benzene in ethyl acetate is appropriate for a homolytic process.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation